15 years standards of management control in Poland – evaluation - Piaszczyk, Artur (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The article presents an overview of changes in law concerning management assessment in Poland, as it pertains to public financial institutions in accordance to the implementation of relevant European Union treaties. The subject of examination is the amendment of Public Finances Act from the year 2001. Partial evaluation will be performed on the application of a bill dated from 2009. According to the author, this is mistake, as the original American bill (Sarbanes-Oxley Act) that inspired the European legislation, only requires the management of private firms to file such declarations. Meanwhile Poland decided to have the law apply to public sector as well. The article attempts to evaluate the last 15 years of the currently functioning legal system. Studies have shown that the current supervision system of management assessment is ineffective, ineffectual and largely useless forcing the employees to needlessly rely on risk analysis and resort to costly control mechanisms and procedures
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 478, s. 348-356
Keywords: standards; management control; public finances; unit; standardy; kontrola zarządcza; finanse publiczne; jednostka